Fundamentalism or tradition : Christianity after secularism - Papanikolaou, Aristotle; Demacopoulos, George E.; Appleby, R. Scott, 1956-; Asproulis, Nikolaos; Gallaher, Brandon, 1972-; Griffiths, Paul J.; Guroian, Vigen; Herbel, Oliver; Humphrey, Edith McEwan; Jakelic, Slavica (Orthodox Christianity and contemporary thought., 2020)
Tradition, secularization and fundamentalism-all three categories are contested, yet in their contestation, they shape our sensibilities and are mutually implicated, the one with the others. The discussion around the mutually implicated meanings of the "secular" and "fundamentalism" bring to the foreground more than ever, and in a way unprecedented in the pre-modern context, the question of what it means to think and live as Tradition. The essays in this volume continue both the interrogation of the categories of the "secular" and "fundamentalism," all the while either implicitly or explicitly exploring ways of thinking about tradition in relation to these interrogations